2007
DOI: 10.1055/s-2007-993741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Topical Anti-Inflammatory Activity of Ginger Dry Extracts from Solutions and Plasters

Abstract: In this study the skin permeation and the topical anti-inflammatory properties of ginger extracts were investigated. A commercial ginger dry extract (DE) and a gingerols-enriched dry extract (EDE) were evaluated for their in vivo topical anti-inflammatory activity by inhibition of Croton oil-induced ear oedema in mice. Furthermore, the feasibility of an anti-inflammatory plaster containing DE or EDE was evaluated. Since the in vivo activity was evaluated in mice, the ex vivo skin permeation study was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 7 publications
2
41
0
Order By: Relevance
“…The HMBC experiment also showed the long-range couplings H-1/C-1 , H-1/C-2 , H-1/C-6 , and H-2/C-1 , which indicated that the alkyl chain is linked to the aromatic ring. Therefore, the structure of 1 was again deduced as a sulfonated gingerol derivative, named [8]-gingesulfonic acid (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The HMBC experiment also showed the long-range couplings H-1/C-1 , H-1/C-2 , H-1/C-6 , and H-2/C-1 , which indicated that the alkyl chain is linked to the aromatic ring. Therefore, the structure of 1 was again deduced as a sulfonated gingerol derivative, named [8]-gingesulfonic acid (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the spectroscopic and physical data with those published allowed us to establish the structures of nine known gingerol derivatives, [6] As mentioned above, three sulfonated derivatives of gingerol were isolated from Zingiber officinale, and their structures were established as [8]-gingesulfonic acid (1), [10]-gingesulfonic acid (2), and [6]-gingesulfonic acid (3). However, the stereochemistry at C-5 of 1 -3 is still under investigation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations